Supported Lipid Bilayer Assembly on PEDOT:PSS Films and Transistors. (6th September 2016) - Zhang, Yi; Inal, Sahika; Hsia, Chih‐Yun; Ferro, Magali; Ferro, Marc; Daniel, Susan; Owens, Roisin M.
Abstract : Lipid bilayers are widely employed as a model system to investigate interactions between cells and their environment. Supported lipid bilayers (SLB) with integrated transmembrane proteins are emerging as a preferred platform for sensing applications. Challenges lie in the generation of SLB on surfaces which allow transduction of signals for characterization of lipid bilayer and incorporated transmembrane proteins. For the first time, the formation of SLBs is shown on films of the conducting polymer, poly(3, 4‐ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS), using traditional methods for characterizing lipid bilayer quality and function (QCM‐D, FRAP) combined with impedance spectroscopy. Further, partial formation of SLBs on PEDOT:PSS based organic electrochemical transistors (OECTs) is successfully demonstrated, as well as the ability to integrate and sense the ion pore α‐hemolysin, confirming the sensitivity of the OECT as a transducer of biological membrane function. This work represents a highly promising first step toward the use of such OECTs for functional readout of transmembrane proteins in their native environment. Abstract : Supported lipid bilayers represent an excellent substitute for live cells, to study membrane protein function. For the first time, the integration of biologically functioning supported lipid bilayers is shown, with conducting polymer films and transistors. Traditional methods for characterizing lipid bilayer quality and function are compared with electrical readouts using both impedance spectroscopy and the organic electrochemical transistor. This represents a first, important step toward readout of such systems with organic transistors.